1995
DOI: 10.1002/j.1550-8528.1995.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Biracial Differences in Physical Activity and Body Composition Among Women

Abstract: TUTEN, CHRIS, RICHARD PETOSA, ROGER SARGENT AND ANNE WESTON. Biracial differences in physical activity and body composition among women. Obes Res. 1995;3:313-318. Overweight among black females is almost two times as frequent as among white females. Genetics, caloric intake, and physical activity have been identified as possible explanatory factors. This study assessed the differences in physical activity and body composition in 76 white and 66 black adult females. Black women had significantly higher (p=.OOOl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…With the use of a physical-activity-recall instrument, Tuten et al (20) found that white women had a greater mean physical activity in the previous 24-h time frame than did black women and that black women were significantly more sedentary. Additionally, 2 studies that used the doubly labeled water method (21,22) showed that total daily EE was significantly lower in African American women than in white women, mainly because the African American women had lower physical-activity EEs.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of a physical-activity-recall instrument, Tuten et al (20) found that white women had a greater mean physical activity in the previous 24-h time frame than did black women and that black women were significantly more sedentary. Additionally, 2 studies that used the doubly labeled water method (21,22) showed that total daily EE was significantly lower in African American women than in white women, mainly because the African American women had lower physical-activity EEs.…”
Section: Discussionmentioning
confidence: 99%
“…Fat loss and maintenance of lower equilibrium fat stores also becomes more difficult with age 26. Finally, there is increasing evidence of racial influences on energy balance 27. These biological influences explain much of the variance in body fat in individuals within a given environment, but they do not explain the large population increases which represent the epidemic itself.…”
Section: An Ecological Modelmentioning
confidence: 99%
“…This racial difference may be due to the greater muscle mass (Aloia et al, 1997;Cohn et al, 1977;and Gasperino et al, 1995) and the higher density of the lean body mass component of body composition (Schutte et al, 1984) found in African Americans. These differences are observed despite lower levels of physical activity among African Americans (Tuten et al, 1995). Therefore, it has been suggested that the racial differences in body composition may be due to a greater extent to heritable factors than they are to environment (Oritz et al, 1992).…”
Section: Introductionmentioning
confidence: 97%